Islam and diplomacy: the quest for human security - Kamali, Mohammad Hashim (Pelanduk Publications, 2017)
This Volume is the outcome of the Forum on Islam and Diplomacy conceived and hosted by the International Institute of Advanced Islamic Studies (IAIS) Malaysia, Institute of Diplomacy and Foreign Relations (IDFR) of Malaysia, and The Cordoba Foundation (TCF), UK, which convened in Kuala Lumpur on May 16th–17th 2013, with the cooperation of the Diplomatic Institute of The State of Qatar. This collaborative effort marks our common commitment to promote realistic engagement with the neglected topic of Peace and Security in Islamic teachings, and work towards a realistic appraisal of Islam’s relevance for human well-being and security. Islam possesses a very rich tradition of legal, ethical and spiritual thought and practice privileging Peace Making and Peace Building. We are convinced this tradition remains directly relevant for ensuring a global system of harmonious relations in our time. The scholars and officials whose remarks are collected here throw light on both Islamic theory and Muslim practices of peace.